Placental lipoprotein lipase DNA methylation alterations are associated with gestational diabetes and body composition at 5 years of age. Issue 8 (3rd August 2017) - Gagné-Ouellet, Valérie; Houde, Andrée-Anne; Guay, Simon-Pierre; Perron, Patrice; Gaudet, Daniel; Guérin, Renée; Jean-Patrice, Baillargeon; Hivert, Marie-France; Brisson, Diane; Bouchard, Luigi
ABSTRACT: Gestational diabetes mellitus (GDM) is associated with obesity in childhood. This suggests that consequences of in utero exposure to maternal hyperglycemia extend beyond the fetal development, possibly through epigenetic programming. The aims of this study were to assess whether placental DNA methylation (DNAm) marks were associated with maternal GDM status and to offspring body composition at 5 years old in a prospective birth cohort. DNAm levels were measured in the fetal side of the placenta in 66 samples (24 from GDM mothers) using bisDNA-pyrosequencing. Anthropometric and body composition (bioimpedance) were measured in children at 5 years of age. Mann-Whitney and Spearman tests were used to assess associations between GDM, placental DNAm levels at the lipoprotein lipase ( LPL ) locus and children's weight, height, body mass index (BMI), body fat, and lean masses at 5 years of age. Weight, height, and BMI z-scores were computed according to the World Health Organization growth chart. Analyses were adjusted for gestational age at birth, child sex, maternal age, and pre-pregnancy BMI. LPL DNAm levels were positively correlated with birth weight z-scores (r = 0.252, P = 0.04), and with mid-childhood weight z-scores (r = 0.314, P = 0.01) and fat mass (r = 0.275, P = 0.04), and negatively correlated with lean mass (r = −0.306, P = 0.02). We found a negative correlation between LPL DNAm and mRNA levels in placenta (r = −0.459; P < 0.001), which highlights the regulation of transcriptional activity by these epivariations. We demonstrated that alterations in fetal placental DNAm levels at the LPL gene locus are associated with the anthropometric profile in children at 5 years of age. These findings support the concept of fetal metabolic programming through epigenetic changes.